Witch Trials and Sorcery Processes in Foreign Historiography: New Perspectives and Angles of View (Theatrum historiae, 2017)
The present study is devoted to historiographical foreign production related to the issue of processes with witches and female sorcerers, especially to the development of linguistically German and English research within approximately the last thirty years. The transformation of individual theories and methodological approaches to the topic using other scientific disciplines, such as anthropology, ethnology or psychology is reflected. Also some questions concerning, for example, the role of torture or solving the problem whether the processes can be described as a profitable programme of elites are accentuated here. These questions are subsequently partly answered just through the new results of the international research.
Keywords: witchcraft; sorcery; torture; historiography